[Dexter building view of Kennedy Library] - P. K. Phillips::::::photographer::: (1978)
View of the crane used to construction Kennedy Library, from the opposite side of the Walter F. Dexter Building (Building 34). Campus members are visible, standing in various places near Dexter and its adjacent street. The library is not visible behind Dexter.